Synthesis and Anti-Tumor Effects of Novel Pomalidomide Derivatives Containing Urea Moieties - Yajie Guo; Xi Wang; Zhenzhen Wang; Longfei Mao; Jiahao Wang; Lizeng Peng; Guiqing Xu (MDPI AG, 2022)
In order to explore novel immunomodulatory agents as anti-tumor drugs, we designed and synthesized a series of new pomalidomide derivatives containing urea moieties. Interestingly, in vitro biological experiments performed in several cancer cell lines showed that some of them displayed potent anti-tumor ability. These novel compounds 5a-5e and 6a-6e demonstrated the best cell growth inhibitive activity in human breast cancer cell lines MCF-7, but weaker inhibitive activity in human hepatocellular carcinoma cell lines Huh7. Moreover, compound 5d had the most powerful effects in this study, with an IC50 value of 20.2 μM in MCF-7. Further study indicated that compound 5d could inhibit cell growth and induce cell death in a concentration-dependent manner. Besides, compound 5d increased cellular ROS levels and induced DNA damage, thereby potentially leading to cell apoptosis. These observations suggest that the novel pomalidomide derivatives containing urea moieties may be worth further investigation to generate potential anti-tumor drugs.